2009
DOI: 10.2105/ajph.2008.143958
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Americans and Frailty: Findings From the Hispanic Established Populations Epidemiologic Studies of the Elderly

Abstract: Objectives-We examined frailty, particularly how diabetes and obesity impact disability and morbidity in Mexican American older adults.Methods-We studied the trajectory of frailty over 10 years in 2,049 Mexican Americans participating in the Hispanic Established Populations Epidemiologic Studies of the Elderly. A frailty index based on weight loss, exhaustion, grip strength, walking speed, and physical activity was computed and data were collected on sociodemographic and health status, comorbidities and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
158
0
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(195 citation statements)
references
References 30 publications
20
158
0
17
Order By: Relevance
“…Our findings are similar to the results from previous studies suggesting that frailty is strongly associated to disability (table 3), but they are not the same because 68% and 87% of the subjects who had some dependency to basic and instrumental activities of daily living were not frail (3,4,8,27,28). As in previous studies, frailty was strongly associated with comorbidity, especially symptomatic cardiovascular diseases (29) and cognitive impairment.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are similar to the results from previous studies suggesting that frailty is strongly associated to disability (table 3), but they are not the same because 68% and 87% of the subjects who had some dependency to basic and instrumental activities of daily living were not frail (3,4,8,27,28). As in previous studies, frailty was strongly associated with comorbidity, especially symptomatic cardiovascular diseases (29) and cognitive impairment.…”
Section: Discussionsupporting
confidence: 88%
“…The results from the studies by Fried et al, 8 Woods et al, 28 Ávila-Funes et al 29 and Ottenbacher et al 30 demonstrated significant correlations (P < 0.05) between female sex, advanced age and frailty. Ottenbacher et al 30 only found an association between female sex and frailty, while Purser et al 9 also found that the five-times sit-tostand test was a strong predictor of frailty. These findings show the relevance and applicability of this study, which makes it simpler to identify frailty risk groups through an easily applied lower-limb muscle strength test.…”
Section: Discussionmentioning
confidence: 92%
“…When screened for in a population of people with DM, the prevalence of frailty also varied and was reported to be between 5-48% [31]. Several studies have shown that older DM patients were more likely to be frail than their non-DM counterparts [19][20][21][32][33][34][35]. These studies also reported that DM patients with frailty had a higher mortality rate than non-frail DM patients, with the presence of frailty an independent risk factor for mortality.…”
Section: Prevalence Of Frailtymentioning
confidence: 99%